Shy radicals : the antisystemic politics of the militant introvert - Ahsan, Hamja 1981-; Power, Nina; Nordin, Rose (London : Book Works, 2020)
Drawing together communiqués, covert interviews, oral and underground history of introvert struggles (Introfada), here for the first time is a detailed documentation of the political demands of shy people. Radicalised against the imperial domination of globalised PR projectionism, extrovert poise and loudness, the Shy Radicals and their guerrilla wing the Shy Underground are a vanguard movement intent on trans-rupting consensus extrovert-supremacist politics and assertiveness culture of the twenty first century. The movement aims to establish an independent homeland - Aspergistan, a utopian state for introverted people, run according to Shyria Law and underpinned by Pan-Shyist ideology, protecting the rights of the oppressed quiet and shy people. Shy Radicals are the Black Panther Party of the introvert class, and this anti-systemic manifesto is a quiet and thoughtful polemic, a satire that uses anti-colonial theory to build a critique of dominant culture and the rising tide of Islamophobia. Shy Radicals author Hamja Ahsan is an artist, curator and activist based in London. He is the Free Talha Ahsan campaign organiser.--Book Works website.
Draft constitution of the Shy People's Republic of Aspergistan -- #OccupyBedroom -- New lexicon of democracy -- Public statement : shy radicals is not a terrorist organisation -- Interview with Amy Littlewood -- Building the shy radical student movement -- Curating shy people : shy radicals film season -- Crisis voices oral history project -- Report from the Inverness delegation -- Ruptures in the extrovert world order -- Allies and coalition partners in the Introfada -- Directory of helpful services -- Axis of resistance of the white man -- Vanguard melancholia : black-black power -- Compass of the extrovert class : eight extrovert identities -- The demand for reparations.
boek
Keywords: Ahsan, Hamja; Introverts; Political manifestos; Political satire, English; Introspection -- Political aspects; Imaginary societies; Great Britain -- Politics and government -- 21st century